Caracterização molecular de Colletotrichum acutatum e C. gloeosporioides associados a citros, por marcadores ISSR - Silveira, Amanda Letícia da [UNESP] (2015)
Postbloom fruit drop of citrus (PFD) is a serious disease of this crop, accounting for high yield losses. Usually, this disease shows to be limiting when there are prolonged rainy periods during plant flowering or when there is intense leaf wetness. Two Colletotrichum species are associated with the disease: C. acutatum and C. gloeosporioides. However, recently, it has been found that, even under not so favorable conditions, the disease has occurred with some frequency; one suspects the involvement of other Colletotrichum species or new adaptation conditions of the described species. This study aimed to determine whether there is another Colletotrichum species associated with PFD and it assess the viability of using molecular markers ISSR for taxonomic characterization of Colletotrichum spp. isolates associated with PFD symptoms in flowers, as well as of leaf tissues and asymptomatic citrus fruits. For this purpose, we used a combination of specific primers, taking into account the ITS region and ISSR molecular markers. ISSR markers have proven to be effective for taxonomic characterization of the Colletotrichum isolates analyzed. The population assessed consisted only of C. acutatum and C. gloeosporioides, discarding the involvement of an additional species, something which converges with records in the literature. We found high genetic diversity among the isolates analyzed, and this also shows to converge as for the phenotypic differences observed under field conditions. However, no relation was found regarding the origin and associated Colletotrichum spp. species. In an unprecedented way, although asymptomatically, we detected the presence of a C. acutatum isolate associated with citrus fruits